El taller: aproximación a sus bondades y límites en las ciencias pecuarias - Alzate Yepes, Teresita (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Within the strategies used in higher education, although sometimes lightly used, is the workshop, the methodology used for excellence by the teachers in many courses, therefore becomes imperative to understand and clarify its scope, advantages and requirements in order to make decisions regarding their implementation, so as not to invalidate or underutilized its potential. In this text we assume the workshop as an empowering technical learning significant in this case, will enroll in didactic model operating.